Evaluation of the Extent of Primary Buccal Mucosal Graft Contracture in Augmentation Urethroplasty for Stricture Urethra: A Prospective Observational Study at a Tertiary Healthcare Centre - A. BhalaguruIyyan; P. Puvai Murugan; Chandranaath C. Alakhananda; B. M. Zeeshan Hameed (Advances in Urology)
Introduction. Buccal mucosal graft (BMG) urethroplasty is considered as gold standard in the treatment of urethral stricture disease. The successful outcome after BMG urethroplasty varies between 66 and 99%. One of the possible causes for failure is BMG contracture. Primary BMG contracture rate is poorly understood and unreported. The present study aimed to evaluate the extent of contracture of buccal mucosa immediately after harvesting. Materials and Methods. This was a prospective observational study conducted in the Department of Urology at our institute between January 2016 and December 2019. All patients with urethral stricture disease undergoing BMG urethroplasty for the first time were enrolled in the study after obtaining informed consent. Demographic and patient clinical profile was noted. Based on the intraoperative urethral stricture size, the preharvest graft was marked on the buccal mucosa and the size was calculated. Postharvest unstretched size of the graft was measured immediately after graft removal from the oral cavity. Alteration in BMG size was analysed using paired t-test. Results. Forty-four patients were included in the study. Mean age of the patient was 53.6 years. Mean stricture length was 7.45 cm (range 4–12 cm). Mean pre- and postharvest BMG size was 8.3 × 1.5 cm and 7.6 × 1.3 cm, respectively. There was a 8.4% decrease in length and 9.5% decrease in width of the buccal mucosal graft. Conclusion. Primary buccal mucosal graft contracture is around 8.4% in length and 9.5% in width. It would be better to mark wider than necessary while harvesting buccal mucosa so that tension-free anastomosis is performed.